2005
DOI: 10.3354/dao066021
|View full text |Cite
|
Sign up to set email alerts
|

Oral l-cysteine ethyl ester (LCEE) reduces amoebic gill disease (AGD) in Atlantic salmon Salmo salar

Abstract: There is a need for the development of alternative therapeutic treatments for amoebic gill disease (AGD) in Atlantic salmon Salmo salar L. to maintain the sustainability of the Tasmanian Atlantic salmon aquaculture industry. This study aimed to assess the effects of the mucolytic drug L-cysteine ethyl ester (LCEE) on marine Atlantic salmon mucus and whether or not it may have a therapeutic advantage for the alleviation of AGD when administered orally. We also aimed to document any physiological consequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
12
1
Order By: Relevance
“…These results clearly contrast those of Roberts and Powell (2005b) and Roberts (2004) who demonstrated that AGD was retarded with branchial lesions developing at approximately half as fast as in controls as a result of feeding LCEE at the same concentration and formulation as in our present study. One explanation may be that the period of feeding NAC prior to inoculation with Neoparamoeba spp.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results clearly contrast those of Roberts and Powell (2005b) and Roberts (2004) who demonstrated that AGD was retarded with branchial lesions developing at approximately half as fast as in controls as a result of feeding LCEE at the same concentration and formulation as in our present study. One explanation may be that the period of feeding NAC prior to inoculation with Neoparamoeba spp.…”
Section: Discussioncontrasting
confidence: 99%
“…One explanation may be that the period of feeding NAC prior to inoculation with Neoparamoeba spp. was inadequate (Roberts and Powell 2005b used a 14‐d prefeeding period). However, viscosity measurements of the cutaneous mucus from fish at the point of inoculation (Day 0) and end of the study (Days 14 and 19 for rainbow trout and Atlantic salmon, respectively) showed overall reduction in mucus viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro screening of various antiparasitic drugs and oxidative disinfectants had identified several compounds of interest (Howard & Carson , ; Powell et al . , ; Roberts & Powell ). However, producing an unequivocal resolution of AGD (compared to FW treatment) that is transferable to the commercial farming environment has proven elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which freshwater bathing produces a therapeutic effect, however, is poorly understood. Such knowledge would aid research and development into improved and alternative treatments for fish gill diseases, including mucolytic drugs (Yang & Albright, 1994; Roberts & Powell, 2005 a ).…”
mentioning
confidence: 99%